2012
DOI: 10.1515/jpm-2012-0097
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risks after IVF and ICSI

Abstract: Pregnancies that occur after infertility treatment, particularly after assisted reproduction, constitute high-risk pregnancies. Occurrences of conditions such as high blood pressure, preeclampsia, growth retardations and bleeding are higher in comparison with the norm of spontaneously entered pregnancies. The rate of premature births and the frequency of intrauterine deaths are much higher than the average for all pregnancies. Furthermore, pregnancies resulting from in -vitro fertilisation (IVF) have signifi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
(42 reference statements)
1
34
1
5
Order By: Relevance
“…While the present thesis found that the risk of preeclampsia was increased in the women who had undergone IVF treatment, the regression analyses did not show an association between preeclampsia and PPP nor between IVF pregnancies and PPP. In addition, the results of Study II confirmed the results of previous studies in showing that the risk of most pregnancy and delivery complications, including PTB (8)(9)(10)(11)13) and delivery by caesarean section (8,10,11), which some studied have identified as risk factors for PPP (97,119), was higher in the women who had given birth after IVF treatment compared to those who had conceived spontaneously. However, no associations were found between these complications and PPP in the logistic regression analyses.…”
Section: Principal Findings In Relation To Previous Research Postpartsupporting
confidence: 83%
See 4 more Smart Citations
“…While the present thesis found that the risk of preeclampsia was increased in the women who had undergone IVF treatment, the regression analyses did not show an association between preeclampsia and PPP nor between IVF pregnancies and PPP. In addition, the results of Study II confirmed the results of previous studies in showing that the risk of most pregnancy and delivery complications, including PTB (8)(9)(10)(11)13) and delivery by caesarean section (8,10,11), which some studied have identified as risk factors for PPP (97,119), was higher in the women who had given birth after IVF treatment compared to those who had conceived spontaneously. However, no associations were found between these complications and PPP in the logistic regression analyses.…”
Section: Principal Findings In Relation To Previous Research Postpartsupporting
confidence: 83%
“…The risk of preeclampsia is increased in IVF pregnancies (8,11,13). While the present thesis found that the risk of preeclampsia was increased in the women who had undergone IVF treatment, the regression analyses did not show an association between preeclampsia and PPP nor between IVF pregnancies and PPP.…”
Section: Principal Findings In Relation To Previous Research Postpartcontrasting
confidence: 82%
See 3 more Smart Citations